Aktivitas Ekstrak Etanolik Daun Seligi (Phyllanthus buxifolius (BI.) M.A.) terhadap Kadar HDL dan LDL pada Serum Darah Tikus - Sri Agustiningsih; Titik Sunarni; Fransiska Leviana (Fakultas Farmasi Universitas Setia Budi, 2014)
Seligi (Phyllanthus buxifolius (BI.) M.A.) leaves contain flavonoid, polifenol, and saponin that have antioxidant activity and thought to potentially as antihiperlipidemic. This research was aimed to find out the effect of seligi leaves ethanol extract to increase HDL level and decrease LDL level in white rats. The subject of the research was 30 male white rats in 150-200 gram body weight and 2-3 months age. Rats were divided into 6 groups randomly then were given BR II and water everyday. Group I, II, and III were normal control group, the positive control (simvastatin), and negative control respectively. The treatment group was given seligi leaves extract in doses of 75; 150; and 300 mg/kg bw/day. The tested animal were given cow fat and yolk for two weeks up to hypercholesterolemia state, tested preparation was given on day-14 until the day-28. The HDL and LDL levels were measured on the day-0, 14, and 28 by CHOD-PAP method. The result of researchshowed that seligi leaves ethanol extract orally administration could increase the HDL and decrease the LDL levels of blood serum. Seligi leaf ethanol extract with dose 300 mg/kg bw/day had equal effectiveness to simvastatin.